2000
DOI: 10.3923/pjbs.2000.1901.1903
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Sowing Dates on the Yield of Newly Developed Strain under Climatic Conditions of Ghotki, Sindh

Abstract: Newly developed strain GH-3 was tried against commercial variety Shaheen in sowing date trial over a period of three years to assess the optimum sowing time of the strain under Ghotki conditions. Accordingly 15th May was recorded as optimum sowing time for this area as maximum yield of 1979 kg haG 1 was obtained followed by 1st May and 1st June sowings that produced 1516 and 1491 kg haG 1 seedcotton yield respectively. The lowest yield (1160 kg haG 1 ) was obtained when the crop was sown on 15th June followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Higher seed yield of a number of okra cultivars were obtained from June sowings compared to late July sowings (Shujat et al, 2006). Soomro et al, (2000) while studying on the optimum time of sowing concluded that crop sown from 5 th to 20 th may gave highest yield as compared to early or late sown under Sakrand conditions.…”
Section: Date Of Sowingmentioning
confidence: 99%
“…Higher seed yield of a number of okra cultivars were obtained from June sowings compared to late July sowings (Shujat et al, 2006). Soomro et al, (2000) while studying on the optimum time of sowing concluded that crop sown from 5 th to 20 th may gave highest yield as compared to early or late sown under Sakrand conditions.…”
Section: Date Of Sowingmentioning
confidence: 99%
“…Khan and Gill 1982;Qayyum et al, 1990;Ansari et al, 1991;Arain et al, 2001;Moustafa 2022 andZhang et al, 2022, reported that early sown cotton (15 April to 15 May) gave significantly higher plant height, number of sympodial branches, number of bolls formed, seed cotton weight per plant and seed cotton yield per hectare. Khan et al, 1981;Ansari et al, 1989;Soomro et al, 2000;Kakar et al, 2012 andKeerio et al, 2022 observed that 15 th May is an optimum sown crop gave increased number of bolls per plant, boll weight and seed cotton yield per hectare and they further noticed a remarkable decline in the yield of late sown crop. It has been concluded that boll weight gradually decreased with the delay in sowing time.…”
Section: Introductionmentioning
confidence: 99%
“…Cotton yield can be increased significantly if we know the optimum time for sowing in particular zone. It has been observed that cotton sown earlier or later than its optimum time shows a rapid decline in its yield (Soomro et al, 2000). From the previous research studies, it was observed that the increase in temperature and changes in the rainfall pattern will directly affect the growth and development of cotton crop and resulting in the production of poor-quality cotton in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…It is quite sensitive to climatic situations (Gormus and Yucel, 2002). Cotton seeds were sown before or after the optimal time and conducted poor production (Soomro et al, 2000) as a result of disease and pest problems. Sowing too early relates to risks inclusive of cool ambient and soil temperatures (Pettigrew, 2002;Bozbek et al, 2006), humid climate and physical resistance (Guthrie, 1991), seedling disease, and insect pressure (Pettigrew, 2002).…”
Section: Introductionmentioning
confidence: 99%